Assessing microbial diversity in soil and roots of longan fruit in Son La province, Vietnam - Thi Nhat, Phuong Bui; Nam, Le Quang; Dung, Le Viet; Herrmann, Laetitia; Jalonen, Riina; Lesueur, Didier (2024)
Agricultural productivity is intricately linked to the health and biodiversity of soil, making the study of these components paramount in understanding and enhancing crop production. As the foundation of terrestrial ecosystems, soil health and biodiversity play pivotal roles in nutrient cycling, disease suppression, and overall ecosystem resilience (Berendsen et al., 2012). Recognizing the significance of these factors in sustaining crop yields, the current study focuses on assessing microbial diversity in both soil and root of longan fruit (Dimocarpus longan) plantations in Son La Province. Longan is a tropical and sub-tropical plant. In Vietnam, longan is grown quite popularly in all parts of the country from North to South. Due to its high economic efficiency, in recent years, the cultivated longan area has grown rapidly. The research focuses on different treatments on longan plantation in Son La province, including: